The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12199-021-00983-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and C virus infection among healthcare workers in Africa: a systematic review and meta-analysis

Abstract: Background Healthcare workers are at risk of acquiring hepatitis B and C virus infections through patients’ blood and bodily fluids exposure. So far, there is no pooled data that shows the prevalence of HBV and HCV among health care workers in Africa. This study aimed to determine the pooled prevalence of hepatitis B and C infections among health care workers in Africa. Methods Studies reporting the prevalence of HBV and HCV were identified from ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 83 publications
(50 reference statements)
1
14
4
Order By: Relevance
“…Saharan Africa up to 2020 (6.81%; 95% CI 5.67-7.95) [23] and is above the prevalence found in the meta-analysis that included Asian countries, 4.0% (95% CI: 0.01-0.07) [24]. In Mozambique, although there are no national data for HBV prevalence, the HBsAg prevalence (4.7%) found in this study is similar to those recently found in Beira City among blood donors approved for donation (4.5%) [25] and in Maputo City (southern Mozambique) among pregnant women (4.0%).…”
Section: Plos Onementioning
confidence: 99%
“…Saharan Africa up to 2020 (6.81%; 95% CI 5.67-7.95) [23] and is above the prevalence found in the meta-analysis that included Asian countries, 4.0% (95% CI: 0.01-0.07) [24]. In Mozambique, although there are no national data for HBV prevalence, the HBsAg prevalence (4.7%) found in this study is similar to those recently found in Beira City among blood donors approved for donation (4.5%) [25] and in Maputo City (southern Mozambique) among pregnant women (4.0%).…”
Section: Plos Onementioning
confidence: 99%
“…Viral hepatitis is challenging the health condition of the people around the world and considered the cause of solemn health problem for the human kind in the 21 th century [1][2][3]. In the globe, there are two well-known forms of chronic hepatitis, and this corresponds to hepatitis B virus (HBV) and hepatitis C virus (HCV).…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of HBV infection in Africa is averagely more than 10% while pooled HBV prevalence in HCW was 6.81% (95% CI 5.67-7.95) classifying the region as one of high endemic area (2)(3)(4)(5). In 2007, the Prevalence of HBV infection in Kenya was estimated to be 2-5%, while 31% of the Kenyan population was found to have been previously exposed to HBV (6).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, it is estimated that 257 million people are living with chronic hepatitis B (CHB) viral infection, HBV epidemic mostly affects WHO African and Western Pacific Regions (1). Prevalence of HBV infection in Africa is averagely more than 10% while pooled HBV prevalence in HCW was 6.81% (95% CI 5.67–7.95) classifying the region as one of high endemic area (25). In 2007, the Prevalence of HBV infection in Kenya was estimated to be 2– 5%, while 31% of the Kenyan population was found to have been previously exposed to HBV (6).…”
Section: Introductionmentioning
confidence: 99%